Optimizing resource and restauration scheduling for power distribution systems after a natural hazards a case study with volcanic lahars. - Llumigusín Cachipuz, Grace Alexandra (2022)
High impact low probability events (HILP) such as natural hazards significantly affect the infrastructure of power distribution systems (PDS) leading to considerable social and economic loss. This paper presents a novel methodology for optimizing resource and restoration scheduling in PDS after a natural hazards focusing on reducing operational costs during PDS recovery. The proposed methodology includes a mixed integer linear programming optimization problem in which a DC optimal power flow model is solved. The proposed methodology was evaluated in the IEEE 34-node test feeder and in a real-world case in two PDS: the San Rafael and Salcedo feeders in Cotopaxi Ecuador. The results show the effectiveness of the proposed methodology compared with traditional recovery criteria.